An Empirical Evaluation of Theories of Saving - Guthrie, Harold W. (The Review of Economics and Statistics, 1963)
The theories of saving presented by Keynes, Duesenberry, and Friedman use three different measures of income to explain saving, and each theory has been supported by empirical evidence. The evidence consists of tests of a wide variety of hypotheses contained within or derived from the theories. The tests use many different kinds of data. The objective of this paper is to submit the basic behavioral hypotheses of each theory to a common test on constant data. The results show that the theories are equally acceptable on empirical grounds.